2015
DOI: 10.1371/journal.pone.0122151
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Site Clinical Evaluation of DW-MRI as a Treatment Response Metric for Breast Cancer Patients Undergoing Neoadjuvant Chemotherapy

Abstract: PurposeTo evaluate diffusion weighted MRI (DW-MR) as a response metric for assessment of neoadjuvant chemotherapy (NAC) in patients with primary breast cancer using prospective multi-center trials which provided MR scans along with clinical outcome information.Materials and MethodsA total of 39 patients with locally advanced breast cancer accrued from three different prospective clinical trials underwent DW-MR examination prior to and at 3–7 days (Hull University), 8–11 days (University of Michigan) and 35 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 65 publications
3
57
0
Order By: Relevance
“…Such cytotoxic changes precede changes in tumor size or perfusion, suggesting DWI has potential to provide early indication of treatment efficacy. In support of this theory, a growing number of clinical studies have demonstrated that treatment-induced changes in breast tumor ADC values can differentiate responders and non-responders early in the course of treatment, after only the first cycle of chemotherapy [4244], Figure 4.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Such cytotoxic changes precede changes in tumor size or perfusion, suggesting DWI has potential to provide early indication of treatment efficacy. In support of this theory, a growing number of clinical studies have demonstrated that treatment-induced changes in breast tumor ADC values can differentiate responders and non-responders early in the course of treatment, after only the first cycle of chemotherapy [4244], Figure 4.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…38,39 A multisite trial found that increased ADC observed early in the course of NAT is predictive of response. 40 These changes are better predictors of eventual pathological tumor response to therapy than measurements of tumor diameter or volume. 41 Furthermore, breast cancer patients with lower ADC prior to the initiation of NAT were more likely to exhibit a decrease in tumor volume during treatment.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…Quality control is much needed to ensure accurate quantitation of diffusion-weighted MRI (DWI) measurements for clinical assessments (4), the importance of which is further substantiated by the bias in diffusion measurements recently observed in a multicenter trial (7). Similarly, Min et al summarized several studies that determine a threshold ADC value between benign and malignant breast tumors (8): the reported thresholds ranged from 0.85 × 10 −3 m 2 /s to 1.48 × 10 −3 m 2 /s, which is too broad to be used clinically.…”
Section: Introductionmentioning
confidence: 99%